Role of asprosin and meteorin-like peptide in progression of actinic keratosis to squamous cell carcinoma - Inan Yuksel, Esma; Cicek, Demet; Demir, Betul; Kocaman, Nevin; Calik, Ilknur; Kuloglu, Tuncay (Taylor & Francis Ltd, 2024)
Squamous cell carcinoma (SCC) often develops from an underlying premalignant lesion. Factors that affect the progression of actinic keratosis (AK) to invasive SCC are not fully known. Asprosin (ASP) and meteorin-like peptide (METRNL) are adipokines that are involved primarily in glucose metabolism. We investigated the expression of ASP and METRNL in AK and SCC to evaluate the role of these adipokines in the development of SCC. We used 15 SCC specimens, 12 AK specimens and 12 healthy control skin specimens. ASP and METRNL protein expression in tumor and surrounding tissue was evaluated using immunohistochemistry. ASP expression in tumor tissue was significantly greater in the SCC group than in the control and AK groups, but it did not differ significantly between the AK and control groups. A positive correlation was observed for both ASP and METRNL expressions between tumor tissue and adjacent epidermis, hair follicles, sebaceous gland, eccrine gland, inflammatory cells and vascular structures. ASP and METRNL may exert pro-tumor effects toward development of invasive SCC. The expression intensity of ASP and METRNL can be used as a biomarker of risk of progression to SCC.
Keywords: Actinic keratosis; asprosin; carcinogenesis; human; immunohistochemistry; meteorin-like peptide; squamous cell carcinoma